LIBRARY USER BEHAVIOR AND INFORMATION LITERACY TRANSFORMATION THROUGH AI IN THE POSTGRADUATE READING ROOM, UNIVERSITAS AIRLANGGA - Moch Rizqi Aprillyawan; Gustina Erlianti; Ersafitri Rachmadiani (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
University libraries play a vital role in supporting the implementation of the Tri Dharma of Higher Education, which encompasses education, research, and community service. The advancement of digital technology has transformed library users' behavior in accessing and utilizing information, particularly through the adoption of Artificial Intelligence (AI). This study aims to describe user behavior in the process of literacy transformation mediated by AI at the Reading Room of the Postgraduate School, Universitas Airlangga. The research employed a qualitative descriptive approach with data collected through interviews and observations involving five informants, consisting of master's and doctoral students. The findings indicate that the integration of AI enhances efficiency, effectiveness, and accuracy in information retrieval. Library users utilize AI not only as a technical tool but also as an analytical aid to develop comprehension and digital literacy skills. However, challenges remain, such as overreliance on AI systems and limited ability to evaluate the validity of information. The study concludes that strengthening AI literacy among the academic community is crucial to ensure that technology is used critically, ethically, and productively to support academic activities